Odpowiedzi

2010-02-08T21:40:31+01:00
Odpowiedź na a)
2x-1+4x=2+8x-5
2x+4x-8x=-5+2+1
6x-8x=-5+3
-2x=-2/:(-2)
x=1

b)
2x-7-[3-2x-2+4x]=x-11
2x-7-3+2x+2-4x=x-11
2x+2x-4x-x=-11-2+3+7
-x=-12+10
-x=-2/:(-)
x=2
1 5 1
Najlepsza Odpowiedź!
2010-02-08T21:49:29+01:00
A)2x-1+4x=2+8x-5/-8x+1
-2x=-2/:(-2)
x=1
b)2x-7-[3-2x-2+4x]=x-11
2x-7-3+2x+2-4x=x-11/+7+3-2-x
-x=-3/:(-1)
x=3
c)x/3 - 5/6 = 1/12 - x/2/*12
4x-10=1-6x/+6x+10
10x=11/:10
x=11/10
d)0,7x - 3 +1,1x = -2,1x + 0,6/+3+2,1x
4x=3,6/:4
x=0,9
e) x - 1i1/2 - 1/2x = 2+1/4x - 5/6
x-3/2-1/2x=2+1/4x-5/6/*12
12x-18-6x=24+3x-10/-3x+18
3x=32/:3
x=32/3
1 5 1